Understanding the unintended consequences of online teaching - Rudman, R. J. (South African Journal of Higher Education, 2021)
In March 2020, South Africa entered a hard lockdown and students and academics, were forced to transition into the fully (emergency) online remote learning space. Lecturers innovated, adapted and learnt how to use many new tools in a short period of time. Despite the changed context in which lecturers find themselves, the traditional academic and professional expectations on staff remain unchanged. Lecturers had to balance personal and professional decisions as well as disruptive technologies. This, with the added responsibility for the governance of these technologies and the uncertainties they represent. Each lecturer accepted a set of risks associated with online teaching. The purpose of this article is to outline and reflect on the problems and challenges relating to streaming and recording lecturers. Online education works effectively in developed countries. It faces practical issues at a scale that traditional learning does not. Notwithstanding these practical issues, there are additional fundamental downsides teaching online which gather around three themes: changes in teaching practices, changes to the student experience, and the re-shaping of institutional strategy and responsibilities specifically relating to this new digital environment.